Structure and Function of Pancreatic Lipase-Related Protein 2 and Its Relationship With Pathological States - Zhu, Guoying; Fang, Qing; Zhu, Fengshang; Huang, Dongping; Yang, Changqing (Frontiers in Genetics, 2021)
Pancreatic lipase is critical for the digestion and absorption of dietary fats. The most abundant lipolytic enzymes secreted by the pancreas are pancreatic triglyceride lipase (PTL or PNLIP) and its family members, pancreatic lipase related protein 1 (PNLIPRP1or PLRP1) and pancreatic lipase related protein 2 (PNLIPRP2 or PLRP2). Unlike the family’s other members, PNLIPRP2 plays an elemental role in lipids digestion, especially for newborns. Therefore, if genetic factors cause gene mutation, or other factors leading to non-expression, it may emerge effect on the fat digestion and absorption, on the susceptibility to pancreas and intestinal pathogens. In this review, we will summarize what is known about the structure and function of PNLIPRP2, the levels of PNLIPRP2 and associated with various pathological states.